Scattered Pieces Of The New Order Reflected In Okky Madasari's The Years Of The Voiceless (2013) - Nusara, Rohimawan Valda, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The research aim it (1) describing the New Order in the history of Indonesia, (2) describing the New Order in The Years of The Voiceless Novel written by: Okky Madasari, (3) describing point of view from Okky Madasari in The Years of the Voiceless novel. In accordance with the research aim determined, the research uses qualitative research method by using literature historicism approach. The data source consist of primary and secondary data sources. The primary data source is The Years of the Voiceless novel and secondary data suorce is books or any information related to the material. The data colleted to be analyzed by using interactive model with the data collection, data reduction, data display and conclusion drawing. From the research invention result can be concluded. (1) based on the social historical background of the New Order, it shows that differences between the history and literary books. (2) based on the New Order related in The Years of the Voiceless novel. Okky shows the reality of life under authoritarian rule and biography of the author herself, greatly affect the figures and the background of life. (3) based on the point of view. Okky use two first- person perspective. Both figures is used to represent the views of the social, political and historical events. Key words: New Order, Historicism, The Years of the Voiceless novel.